Pengaturan Sertifikasi Halal bagi Rumah Pemotongan Hewan (RPH) di Indonesia - Sandela, Ilka; Yuana, Adella; Sari, Putri Kemala (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2023)
Halal certification is a series of processes that must be fulfilled by slaughterhouses. The aim is to provide comfort, security, safety and certainty of the availability of halal meat for the community, as well as increasing added value for business actors to produce and sell halal meat products. This research examines the provisions regarding halal certification rules for slaughterhouses in Indonesia, the halal certification mechanism and the consequences for slaughterhouses that are not halal certified. The research method used is the normative juridical method, namely research that focuses on legal norms contained in statutory regulations. The research results show that the provisions for halal certification for slaughterhouses in Indonesia are regulated in Law Number 33 of 2014 concerning Halal Product Guarantees, Law Number 6 of 2023 concerning Determination of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation, Government Regulation Number 39 of 2021 concerning the Implementation of the Halal Product Guarantee Sector, Decree of the Minister of Religion Number 748 of 2021 concerning Types of Products that must be halal certified, and detailed guidelines are regulated in the Decree of the Head of the Halal Product Guarantee Organizing Agency Number 77 of 2023 concerning Guidelines for Implementing the Product Guarantee System Halal in Slaughtering Ruminants and Poultry. The halal certification mechanism consists of the manager or business operator of the slaughterhouse registering and attaching the required documents; BPJPH will examine the requirements that have been attached; Next, an audit and inspection of the product will be carried out, submitting the inspection results to the MUI for a fatwa to be issued; and issue a halal certificate if it passes the audit. The consequences for slaughterhouses that do not implement halal product guarantees are that they will receive administrative sanctions in the form of reprimands, written warnings and revocation of halal certificates for those who already have halal certificates. The author suggests that these consequences be added in the form of slaughterhouses that do not have a halal certificate not being allowed to operate and slaughtered meat being prohibited from circulating.